Metabolomic insights into late-life depression: a systematic review - Yao Gao; Jian-Zhen Hu; Zhong-Ping Wen; Tao Dong; Xin-Zhe Du; Zhi-Fen Liu; Sha Liu (BMC Geriatrics)
Abstract Late-life depression (LLD) is a prevalent mental health issue that significantly impacts the quality of life in the elderly population. In recent years, metabolomics has emerged as a novel research tool, offering fresh insights into the molecular mechanisms underlying LLD. This systematic review synthesizes metabolomic studies from January 2004 to March 2024, aiming to identify differential metabolites, explore diagnostic and predictive potential, and investigate aberrant metabolic pathways in LLD. A total of 12 relevant studies were included, revealing differential metabolites such as amino acids and fatty acids, as well as associated metabolic pathways. The study’s findings provide insights into the prediction and diagnosis of LLD, highlighting the multifaceted metabolic disturbances associated with the condition. By synthesizing existing literature, we highlight the importance of metabolomic research in identifying biomarkers for LLD and potential therapeutic targets, addressing current gaps in understanding the pathophysiology of this condition.